Postural Kyphosis, Shoulder Function, and Work Duration as Predictors of Shoulder Pain among Academic Staff: A Cross-Sectional Study: Kifosis Postural, Fungsi Bahu, dan Durasi Kerja sebagai Prediktor Nyeri Bahu pada Staf Akademik: Studi Cross-Sectional - Andi Fadhilah Tenriwulan; Bagas Anjasmara; Suci Ariani (Academia Open, 2023)
This cross-sectional study aimed to investigate the relationship between thoracic kyphosis posture, shoulder function, work duration, and the occurrence of shoulder pain among academic staff at Universitas Muhammadiyah Sidoarjo. A purposive sampling technique was employed to select 21 participants. Thoracic posture was measured using an inclinometer, shoulder function was assessed using the Constant-Murley Score, and muscle strength was evaluated with a hand dynamometer grip power test. The results revealed a significant correlation between thoracic kyphosis posture, shoulder function, work duration, and the occurrence of shoulder pain (r: 0.7±0.001, r: 0.6±0.003, r: 0.8±0.001, respectively). This study highlights the crucial role of posture, shoulder function, and work duration in contributing to shoulder pain among academic staff, emphasizing the need for ergonomic interventions and preventive measures to promote musculoskeletal health in this population. Highlights: Significant Correlation: The study establishes a strong and significant correlation between thoracic kyphosis posture, shoulder function, and work duration with the occurrence of shoulder pain among academic staff. Functional Impact: Shoulder function, as assessed by the Constant-Murley Score, plays a pivotal role in the development of shoulder pain, shedding light on the importance of maintaining optimal shoulder mobility and strength. Ergonomic Implications: The findings underscore the need for targeted ergonomic interventions and preventive strategies to mitigate shoulder pain among academic staff, emphasizing the importance of promoting musculoskeletal well-being in prolonged static work settings. Keywords: Postural Kyphosis, Shoulder Function, Work Duration, Shoulder Pain, Academic Staff